Towards a Fuller Assessment of the Economic Benefits of Reducing Air Pollution from Fossil Fuel Combustion: Per-Case Monetary Estimates for Children’s Health Outcomes - Shea, E. (Environ Res, 2019)
BACKGROUND: Impacts on children’s health are under-represented in benefits assessments of policies related to ambient air quality and climate change. To complement our previous compilation of concentration-response (C-R) functions for a number of children’s health outcomes associated with air pollution, we provide per-case monetary estimates of the same health outcomes. OBJECTIVES: Our goal was to establish per-case monetary estimates for a suite of prevalent children’s health outcomes (preterm birth, low birth weight, asthma, autism spectrum disorder, attention-deficit/hyperactivity disorder, and IQ reduction) that can be incorporated into benefits assessments of air pollution regulations and climate change mitigation policies. METHODS: We conducted a systematic review of the literature published between January 1, 2000 and June 30, 2018 to identify relevant economic costs for these six adverse health outcomes in children. We restricted our literature search to studies published in the U.S., with a supplemental consideration of studies from the U.K. and prioritized literature reviews with summary cost estimates and papers that provided lifetime cost of illness estimates. RESULTS: Our literature search and evaluation process reviewed 1,065 papers and identified 12 most relevant papers on per-case monetary estimates for preterm birth, low birth weight, asthma, autism spectrum disorder, and attention-deficit/hyperactivity disorder. Details are presented in full. We separately identified estimates of the lost lifetime earnings associated with the loss of a single IQ point. The final per-case cost estimates for each outcome were selected based on the most robust evidence. These estimates range from $23,573 for childhood asthma not persisting into adulthood to $3,109,096 for a case of autism with a concurrent intellectual disability. CONCLUSION: To our knowledge, this is the first time that the child-specific health outcomes of preterm birth, low birth weight, asthma, autism spectrum disorder, attention-deficit/hyperactivity disorder, and IQ reduction have been systematically valued and presented in one place. This is an important addition to the body of health-related valuation literature as these outcomes have substantial economic costs that are not considered in most assessments of the benefits of air pollution and climate mitigation policies. In general, however, the available per-case estimates presented here did not incorporate the broad societal and long-term costs and are likely underestimates. Although our context has been air pollution and climate policies, the per-case monetary estimates presented here can be applied to other environmental exposures. Fuller assessments of health benefits to children and their corresponding economic gains will improve decision-making on environmental policy.